Peranan Ajaran Niti Sastra Dalam Membangun Jiwa Kepemimpinan Generasi Muda - Wira Diputra, Gede Bagus (PT. ALHAFI BERKAH INDONESIA, 2024)
A leader is someone who has the responsibility to provide direction, motivate and manage a group or organization. Leaders have an important role in guiding and leading people towards a common goal. The young generation is a hope and reflection in predicting what the future condition of our nation will be like in the future, Therefore, the character of the younger generation has a great influence on the future of the nation. To maintain and improve the progress of this nation, coaching the younger generation is a serious matter, In the midst of technological advances, especially advances in social media, it certainly greatly influences people's mindset, especially the younger generation. For this reason, Niti Sastra's role in shaping the spirit of leadership in the younger generation is very important, so that the moral ethics of future leaders in leading the nation in the future can be saved. In this article discusses leadership qualities and values ​​in Niti Sastra that should be possessed and implemented by the younger generation.